Factors Affecting the Outcomes of the Nursing and Midwifery Licensing Examination among Nursing Graduates of Kuakarun Faculty of Nursing: A Qualitative Study - Pongsathonviboon, Khachee; Lhaosupab, Niramon; Panthongchai, Surisa; Soowit, Boontiva; Akkarawongvisit, Chutarat (Journal of The Royal Thai Army Nurses, 2025)
This qualitative research aimed to explore factors influencing the outcomes of the national licensing examination for professional nursing and midwifery (Level 1). The study sample comprised nine nursing graduates who had completed their degree and successfully passed the licensing examination. Data collection employed focus group discussions and semi-structured interviews, together with academic records from 19 relevant courses, totaling 214 datasets. Data were analyzed using content analysis to ensure rigor and credibility. The findings revealed that factors associated with examination performance can be categorized into two main domains. Internal factors included academic achievement in relevant courses, personal motivation, examination attitudes, and prior experiences with subject content. External factors encompassed pre-examination preparation, the organization of the comprehensive examination, and supportive learning environments that fostered knowledge and skill development. The study highlights the importance of enhancing academic readiness, cultivating appropriate attitudes and motivation, and strengthening institutional learning support systems as critical components of examination success. The findings of this study contribute valuable insights for strengthening the preparedness of nursing students undertaking future professional licensing examinations in nursing and midwifery.